RELATIONSHIP OF HYPERTENSION WITH AORTIC CALCIFICATION IN CHEST X-RAY IMAGES OF PATIENTS AT RSUP KEYWORDS HAJI ADAM MALIK MEDAN - Hafiz Nurdiansyah; Elvita Rahmi Daulay; Radar Radius Tarigan (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
Hypertension serves as an independent risk factor for atherosclerosis development and is linked to factors that predispose to aortic calcification. Furthermore, hypertension has the potential to cause the acute rupture of existing plaques by elevating mechanical pressure on them. Chest X-ray imaging is a commonly employed method for identifying aortic calcification during routine examinations. Medial arterial calcification is visualized as radiopaque findings resembling tram-tracks, while calcification within the intima is observed as radiopaque spots.A cross-sectional study involving 92 hypertensive individuals who underwent chest X-ray imaging at RSUP Haji Adam Malik Medan aimed to assess the distribution of study subjects in terms of age, gender, hypertension severity, and aortic calcification degree. Hypertension history was extracted from patients' medical records, and aortic calcification measurements were conducted in the aortic arch by both the researcher and a radiologist. The majority of hypertensive patients were aged over 65, accounting for 40.2% of the sample, with a predominant female population of 57.6%. Stage 1 hypertension was the most prevalent, affecting 52.2% of the subjects, and grade one aortic calcification was the most common, observed in 63% of cases.A weak yet statistically significant positive correlation between hypertension and aortic calcification was identified (p < 0.05; r = 0.196) in the patient population at RSUP Haji Adam Malik Medan.